2022
DOI: 10.3389/fnbeh.2022.924305
|View full text |Cite
|
Sign up to set email alerts
|

Associating Flexible Regulation of Emotional Expression With Psychopathological Symptoms

Abstract: Background: Stressful situations and psychopathology symptoms (e.g., depression and anxiety) shape how individuals regulate and respond to others’ emotions. However, how emotional expressions influence mental health and impact intrapersonal and interpersonal experiences is still unclear.Objective: Here, we used the Flexible Regulation of Emotional Expression (FREE) scale to explore the relationship between emotional expression abilities with affective symptoms and mental health markers.Methods: From a sample o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…23,43,44,67 This is arguably a far too static view on ER, and the more recent view is that expressive suppression increases resilience if applied flexibly and appropriately. [68][69][70] For instance, a recent study found that both the flexible suppression and enhancement of emotion expression was positively associated with general selfefficacy beliefs. 70 Because expressive suppression is also associated with psychopathology, which is negatively associated with SE, the flexibility to which individuals apply expressive suppression may have been a bidirectional confounder in the relationship between expressive suppression and SE in our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,43,44,67 This is arguably a far too static view on ER, and the more recent view is that expressive suppression increases resilience if applied flexibly and appropriately. [68][69][70] For instance, a recent study found that both the flexible suppression and enhancement of emotion expression was positively associated with general selfefficacy beliefs. 70 Because expressive suppression is also associated with psychopathology, which is negatively associated with SE, the flexibility to which individuals apply expressive suppression may have been a bidirectional confounder in the relationship between expressive suppression and SE in our results.…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70] For instance, a recent study found that both the flexible suppression and enhancement of emotion expression was positively associated with general selfefficacy beliefs. 70 Because expressive suppression is also associated with psychopathology, which is negatively associated with SE, the flexibility to which individuals apply expressive suppression may have been a bidirectional confounder in the relationship between expressive suppression and SE in our results. Nevertheless, expressive suppression was excluded from subsequent analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of a novel approach, the time–frequency decomposition of heart rate variability, has gained attention in the evaluation of the abnormal fear learning that characterizes several neurological and psychiatric disoders [ 112 ]. Moreover, several studies have suggested the effectiveness of non-invasive brain simulation to interfere and modulate the abnormal activity of neural circuits, such as amygdala–medial prefrontal cortex (PFC) and hippocampus, involved in the acquisition and consolidation of emotional memories, which are altered in psychiatric disorders, such as fear-related disorder including anxiety disorder, phobias, post-traumatic stress disorder (PTSD), or depression [ 113 , 114 , 115 , 116 ] ( Table 1 ).…”
Section: The Tryptophan–kynurenine Metabolic Systemmentioning
confidence: 99%
“…The Psychological Flexibility component includes a sub-process called Emotional Regulation Flexibility (ERF) ( Aldao et al, 2015 ; Burton and Bonanno, 2016 ; Quattropani et al, 2022 ). Emotion Regulation Flexibility refers to the ability to implement and switch between emotion regulation strategies that are synchronized with contextual demands ( Aldao et al, 2015 ; Goubet and Chrysikou, 2019 ; Cobos-Sánchez et al, 2020 ; English and Eldesouky, 2020 ; Gonzalez-Escamilla et al, 2022 ).…”
Section: From Flexibility To Mental Flexibility: O...mentioning
confidence: 99%